Changes in body mass index in different periods of infants born to diabetic and non-diabetic mothers (KYAMC Journal, 2018)
Background: The growth of infants born to diabetic mothers is at greater risks because of their pregnancy related complications.Objectives: This study concerns comparison of BMI changes in different periods of infants born to pre-diabetic mothers (DM) and gestational diabetic mothers (GDM) with control infants born to apparently healthy non-diabetic mothers (NDM).Materials & Methods: This study comprising 251 newbornmother pairs (n: DM=86; GDM=86 and NDM=79) recruited from the Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka.Results: BMI at birth was significantly higher for DM (BMI: 13.3±0.2 vs.12.6±0.2; p=0.003) and GDM (BMI: 13.7±0.2 vs.12.6±0.2; p